Judicial activism and judicial restraint in the constitutional adjudication institution of Malaysia - Mokhtar, Khairil Azmin (2019)
Justices of Malaysian’s courts have the constitutional role of upholding the Federal Constitution, rule of law and safeguarding human rights. In dispensing justice, the judges have shown their creativity in dealing with cases of intrusion by the executive and legislature and their willingness to expand the spectrum of human rights in protecting liberties of the individual against the authorities. The attitude is not shared by all judges and certainly not without restraint. It can be observed in the various decision that judges are also aware of their defined role and the limits of their jurisdiction to the extent that some judges have been regarded as positivist and literalists. In addition to its duty to defend liberties of the people the court also been bestowed with the responsibility of safeguarding the right and autonomy of the federating states. Such issues have emerged several times and been dealt with by the courts ever since the inception of the federation. This paper divulges into cases concerning constitutional and human rights issues as decided by the courts whereby traces of judicial activism and judicial restraint could be identified. The challenging task of striking a balance between creativity and subjectivity with obedience and objectivity need to be treated with care and caution in order not to upset other constitutional organs as the backlash is very much felt until today. Initially, the paper set out the structure and feature if constitutional adjudication institution in the country. The discussion that entails focuses on judicial decisions on selected issues concerning the fundamental aspect of the constitution such as the main concepts of the constitution, the relationship between the federal government and the state governments and human rights. It can be observed from these decisions that there are a few strands of judicial approach in dispensing justice by the courts since the Independence of 1957.